HUBUNGAN KADAR KREATININ DAN MIKROALBUMIN PADA PASIEN DIABETES MELLITUS TIDAK TERKONTROL DI KLINIK MEDIA FARMA SAMARINDA - Suryanata Kesuma; Nurul Anggrieni; Nurul Alidasyah (Klinikal Sains : Jurnal Analis Kesehatan, 2022)
Diabetes Mellitus (DM) is a non-communicable disease but is a fairly large health problem in Indonesia today. The HbA1C examination is the gold standard in measuring glycemic levels, while the examination of creatinine and microalbumin levels is one of the parameters used to assess kidney function or diabetic nephropathy. This study aims to determine the relationship between creatinine levels and microalbumin levels in patients with uncontrolled diabetes mellitus at the Media Farma Samarinda Clinic. This study used a cross-sectional design using the Spearman correlation test. The samples in this study were 107 samples with HbA1C levels > 7%. The sampling technique was carried out using quota sampling. The variables measured were levels of HbA1C, creatinine, and microalbumin. The results of this study indicate that the value of p = (0.589) > = (0.05) in the correlation of HbA1C > 7% with creatinine and the value of p = (0.085) > = (0.05) in the correlation of HbA1C > 7% with microalbumin and the value of p = (0.032) > (0.05) on the correlation of creatinine with microalbumin so that H0 is accepted and Ha is rejected. Based on the results of this study, it can be concluded that there is no relationship between creatinine and microalbumin levels in patients with uncontrolled diabetes mellitus at the Media Farma Samarinda Clinic.